ANALISIS PENGENAAN PAJAK FINAL PERUSAHAAN JASA KONSTRUKSI (Studi Kasus pada Perusahaan Jasa Konstruksi di BEI Periode Tahun 2009-2011) - Novitasari, R. A. Annisa; Zulaikha, Zulaikha (Diponegoro Journal of Accounting, 2013)
This research is a case study to analyze the final tax on construction services company listed on the Indonesia Stock Exchange (BEI), are PT. Adhi Karya and PT. Wijaya Karya. The purpose of the study is to determine whether the calculation of corporate income tax liability is in accordance with Government Regulation No. 51 of 2008 jo. Government Regulation No. 40 of 2009 and Act No. 36 of 2008 as well as whether the final taxation of construction company on the Stock Exchange in the tax burden more onerous or otherwise payable outstanding tax burden becomes lighter. Data from this study were obtained from the financial statements and annual reports of construction services company taken from the IDX website. Determination of the sample of this study is fiscal year 2009-2011. The method of analysis used in this research is descriptive quantitative by using different test t-test. The research concludes that the corporate income tax calculations are in accordance with applicable regulations, and the calculation of the final tax burden is higher than the tax burden is not final. It is more burdensome in the income tax liability payable primarily Taxpayers can no longer compensate for the loss the previous year and did not fulfill the principle of fairness in taxation. But the final rates further simplify the calculation and simplify the delivery of income tax.